Fundamental Analysis Based on Earnings Per Share on Divident Payout Ratio to Determine the Prospects of Stock Investment in The Retail Sector - Rosdaliva, Mehilda; Juniyanto, Arfian Nur (Jurnal Keuangan dan Perbankan (KEBAN), 2023)
This study aimed to obtain a more specific and comprehensive explanation of fundamental analysis based on the EPS to DPR ratio in order to determine the prospects for stock investment in retail sub-sector companies. It was expected that readers or investors would gain knowledge and comprehension from the results of this study in order to facilitate their ability to analyze stocks using fundamental analysis in the form of EPS ratio and DPR. The methods used in this study were literature study and observation. Moreover, the data analysis techniques used were in the form of quantitative descriptive analysis and simple linear regression analysis. Furthermore, the financial reports of the stock issuers of MIDI, AMRT, RALS, MYOR, ACES, and CSAP for the 2016–2021 data period were the secondary data sources in this study. The results of this study demonstrated a positive and significant relationship between the impact of variable X (EPS) and variable Y (DPR). Moreover, these results suggested that the EPS and DPR values are strongly associated with determining the future prospects for stock investment in the retail sector. In addition, as a result of the EPS value increase, the DPR value will also experience a significant increase, thereby increasing stock prices and indicating good prospects for growth in stock investment. Therefore, this study may be used as a suggestion for BNI Sekuritas Yogyakarta to encourage customers or investors to invest in stocks in the retail sector, especially MIDI, AMRT, RALS, MYOR, ACES, and CSAP stocks